2003
DOI: 10.1097/01.tp.0000063704.19149.e3
|View full text |Cite
|
Sign up to set email alerts
|

FK778, a powerful new immunosuppressant, effectively reduces functional and histologic changes of chronic rejection in rat renal allografts

Abstract: FK778 effectively reduces functional and histologic chronic kidney allograft rejection in the rat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…In a renal allograft model of chronic rejection in Fischer to Lewis rats, MMF substantially reduced chronic tubulointerstitial damage, fibrointimal hyperplasia and glomerulosclerosis (16), although another study failed to see a suppression of chronic histology sum scores unless sirolimus was added, when a synergistic effect was observed (33). Interestingly, FK778, the active leflunomide metabolite and de novo pyrimidine synthesis inhibitor, also reduced chronic histological changes including the development of tubular atrophy, fibrointimal hyperplasia, transplant glomerulopathy and glomerulosclerosis in the same experimental chronic rejection model (34). In addition, mononuclear cell infiltration, serum allo-specific antibody production and intragraft TGFb mRNA expression was decreased (34).…”
Section: Discussionmentioning
confidence: 99%
“…In a renal allograft model of chronic rejection in Fischer to Lewis rats, MMF substantially reduced chronic tubulointerstitial damage, fibrointimal hyperplasia and glomerulosclerosis (16), although another study failed to see a suppression of chronic histology sum scores unless sirolimus was added, when a synergistic effect was observed (33). Interestingly, FK778, the active leflunomide metabolite and de novo pyrimidine synthesis inhibitor, also reduced chronic histological changes including the development of tubular atrophy, fibrointimal hyperplasia, transplant glomerulopathy and glomerulosclerosis in the same experimental chronic rejection model (34). In addition, mononuclear cell infiltration, serum allo-specific antibody production and intragraft TGFb mRNA expression was decreased (34).…”
Section: Discussionmentioning
confidence: 99%
“…More precisely, it has been shown that FK778 may inhibit SMC proliferation. In various experimental models it has been demonstrated that FK778 effectively attenuates vascular responses to injury by diminishing neointima formation and fibrointimal hyperplasia, perhaps through inhibition of the receptor tyrosine kinase activity in vascular SMC or their progenitors [14,27,28] . Also in our rat model of epigastric vein-to-common femoral artery interposition grafts a daily regimen of 15 mg/kg FK778 significantly reduced IH resulting in a lower percentage stenosis as compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that FK778 inhibits acute rejection in experimental solid organ transplantation. [1][2][3][4][5][6] Furthermore, FK778 shows some mechanisms, which are separate from the blockade of pyrimidine synthesis. FK778 inhibits the DC-derived activation of T-cells via blocking the activation of the transcription factor NF-KB .…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] The substance has been found to be effective and safe in a phase II study in renal transplantation in humans. 7 As the mechanism of graft rejection in solid organ transplantation differs considerably from those in corneal transplantation, it is necessary to evaluate the efficacy of FK778 in preventing corneal graft rejection in an animal model.…”
Section: Introductionmentioning
confidence: 99%